Ellagic acid alleviates adjuvant induced arthritis by modulation of pro- and anti-inflammatory cytokines - Allam, Gamal (Cent Eur J Immunol, 2017)
Rheumatoid arthritis (RA) is a chronic inflammatory disease of unknown aetiology, but it is now clear that pro-inflammatory cytokines play a central role in its pathogenesis. Ellagic acid (EA) has a variety of biological activities including anti-oxidant, anti-inflammatory, and anti-cancer properties. The aim of the present study was to evaluate the potential effect of ellagic acid on the prevention and/or treatment of adjuvant induced arthritis (AIA) model in mice. Ellagic acid treatment was started one week before AIA induction and continued for three weeks after induction of AIA. Ellagic acid treatment significantly (p < 0.01) inhibited foot paw oedematous swelling and attenuated AIA-associated pathology. Ellagic acid significantly (p < 0.01) reduced serum levels of pro-inflammatory cytokines: interleukin 1β (IL-1β), tumor necrosis factor α (TNF-α), and interleukin 17 (IL-17). However, serum levels of IL-10 and interferon γ (IFN-γ) significantly increased (p < 0.01 and p < 0.05, respectively), while serum level of transforming growth factor β (TGF-β) did not significantly alter with EA treatment. In conclusion, these results suggest that EA attenuated AIA-associated pathology in the mouse model by downregulation of pro-inflammatory cytokines and upregulation of anti-inflammatory cytokines.